2014
DOI: 10.1111/1467-9477.12032
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Local, National and EU Knowledge: The Ignorant Public Reassessed

Abstract: Empirical research has repeatedly confirmed the political ignorance of ordinary citizens, but democracy prevails. This article offers a new perspective into this paradox by arguing that typical political knowledge indicators are inadequate because they only measure national‐level knowledge. The study makes two contributions. First, it compares national, local and European Union political knowledge. Second, it does so with a nationally representative dataset, which comes from a survey from Finland (n = 1,020) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 62 publications
3
10
0
Order By: Relevance
“…Previous studies have shown that there are topics, such as social welfare, community‐oriented issues and local politics, that women are significantly more interested in and know more about (Campbell & Winters ; Coffé ; Ferrin et al. ; Rapeli ; Stolle & Gidengil ). If political interest means something different for women than it does for men, then increasing the former's levels of interest may involve increasing the salience of those issues women are generally interested in.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Previous studies have shown that there are topics, such as social welfare, community‐oriented issues and local politics, that women are significantly more interested in and know more about (Campbell & Winters ; Coffé ; Ferrin et al. ; Rapeli ; Stolle & Gidengil ). If political interest means something different for women than it does for men, then increasing the former's levels of interest may involve increasing the salience of those issues women are generally interested in.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Interestingly, while US studies typically find that older people display better political knowledge than younger people (Delli Carpini & Keeter, 2014;Barabas et al, 2014), evidence concerning the relationship between age and EU knowledge is rather mixed. Age and age squared were both non-significant in Rapeli's (2014) 3). We were particularly interested in whether the usual positive effect of age would obtain, given the widespread claim that young people--a majority of whom voted Remain--were betrayed by their parents' and grandparents' generations--a majority of whom voted Leave (Lennard, 2016;Low, 2017).…”
Section: Accepted Manuscriptmentioning
confidence: 91%
“…There is also some evidence that Liberal Democrat supporters have better political knowledge than both Labour and Conservative supporters (Andersen et al, 2002). Of the foregoing characteristics, male gender, better education and stronger political interest are also among the best predictors of EU knowledge (Clark, 2014;Rapeli, 2014). Interestingly, while US studies typically find that older people display better political knowledge than younger people (Delli Carpini & Keeter, 2014;Barabas et al, 2014), evidence concerning the relationship between age and EU knowledge is rather mixed.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…A similar pattern has recently been discovered in regard to the gap between the Latino minority and the White majority in the US (Pérez 2015). Moreover, young people, who have been branded as a particularly ignorant group, are at least as knowledgeable about the European Union as older age cohorts (Rapeli 2014). The conventional measures of general political knowledge therefore seem to suffer from a certain degree of bias that underestimates the sophistication of certain sociodemographic groups.…”
mentioning
confidence: 99%